Near-UV to mid-IR reflectance imaging spectroscopy of paintings on the macroscale - Gabrieli, F. (Sci Adv, 2019)
Broad spectral range reflectance imaging spectroscopy (BR-RIS) from the near UV through the mid–infrared (IR) (350 to 25,000 nm or 28,571 to 400 cm(−1)) was investigated as an imaging modality to provide maps of organic and inorganic artists’ materials in paintings. While visible–to–near-IR (NIR) reflectance and elemental x-ray fluorescence (XRF) imaging spectroscopies have been used for in situ mapping, each method alone is insufficient for robust identification. Combining the two improves results but requires complex data processing. To test BR-RIS, image cubes from early Italian Renaissance illuminated manuscripts were acquired using two spectrometers. Maps of pigments, including trace minerals associated with mined azurite, and their associated binding media were made. BR-RIS has a more straightforward analysis approach as implemented here than visible-to-NIR, mid-IR, or XRF imaging spectroscopy alone and offers the largest amount of macroscale information for mapping artists’ materials by comparison.